Old Home Week Celebrations as Tourism Promotion and Commemoration: North Bay, Ontario, 1925 and 1935 - Noël, Françoise (Urban History Review / Revue d'histoire urbaine, 2008)
AbstractThis paper examines Old Home Week Celebrations held in North Bay, Ontario, in 1925 and 1935 in terms of both tourism promotion and the public use of the past. Tourism promotion in 1925 reflected a booster attitude and the belief that North Bay would soon benefit from the construction of the Georgian Bay Ship Canal. In 1935, the nature of tourism had changed and the major promotional strategy used was to link a visit to the Dionne Quintuplets in Corbeil with travel to North Bay. In 1925 North Bay also celebrated its history, using a pageant parade, celebrated its pioneers, and turned the granting of city status into a public drama. The 1935 Old Home Week celebration, in contrast, lacked focus, but the decentralization of its organization created an opportunity for the French Canadians of North Bay and area to participate in the event to a much greater extent than in 1925 and to commemorate the 400th anniversary of Jacques Cartier’s arrival in Canada. This memorialization reflected their desire for a greater involvement in civic affairs and the monument they erected created a lasting symbol of their presence in the city. Old Home Week celebrations can be used to study both tourism promotion and the social order of the city.